PENGARUH KUALITAS ANC DAN RIWAYAT MORBIDITAS MATERNAL TERHADAP MORBIDITAS MATERNAL DI KABUPATEN SIDOARJO - Nelyta Oktavianisya (Wiraraja Medika : Jurnal Kesehatan, 2016)
Morbidity and mortality in pregnant and labor women are the major problems in developing countries. The maternal mortality rate in sidoarjo district has readed 96.27 per 100,000 live birth in 2013. This aim of this study was to analyze the effect of the quality of ANC and history of maternal moridity to maternal morbidity in Sidoarjo. This study is an analytic observational with case-control design. The samples of this study were 34 pregnant women in the third trimester who experienced maternal morbidity and 34 pregnant women in the third trimester who did not experience maternal morbidity. The data was analyzed by using univariable, bivariable and multivariable analysis with logistic regression. The results of this study confirmed that the quality of the ANC was poor (OR=4,965; 95% CI: 1,547 to 15,927; p=0,007) and the history of maternal morbidity (OR 6,077; 95%CI: 1,433 to 25,773; p=0,014). Thus, the incidence of maternal morbidity increased. The conclusion: the quality of ANC and the history of maternal morbidity affect the occurrence of maternal morbidity. Suggestions can be drawn based on the results of this study. First, health education should be given to women in their productive age. Secoundly, the quality of ANC should be improved by using KSPR (Kartu Skor Pudji Rochjati) to detect early risk of maternal morbidity in women.